High throughput analysis of solute effects on the mechanical behavior and slip activity of beta titanium alloys. (5th January 2018) - Wang, C.Y.; Yang, L.W.; Cui, Y.-W.; Pérez-Prado, M.T.
Abstract: The high-throughput technique of diffusion multiples has been utilized to unveil the effect of solutes on the mechanical properties (yield strength, elastic modulus, hardness), as well as on slip activity, in β (bcc) quaternary Ti alloys. Using this methodology, libraries of [134] Ti-Al-Cr-Mo and [113] Ti-Al-V-Mo single crystals with gradient compositions were generated over distances spanning a few hundred microns and their mechanical properties were probed at room temperature by compression of micropillars milled at selected compositions. Our results evidence that Cr is a more potent strengthener than Mo in Ti-Al-Cr-Mo alloys, and that Mo is very effective in strengthening Ti-Al-V-Mo alloys. Slip activity was measured by observation of slip traces. In all single crystals investigated, irrespective of orientation and composition, plastic strain was accommodated by cross slip between different {110} planes. The specific combination of {110} slip systems that act cooperatively to accommodate strain, as well as the amount of strain accommodated by each slip system, however, is dependent on orientation and on composition. Anomalous {110} slip was observed in the Ti-Al-V-Mo alloys. The incidence of this mechanism was found to increase with increasing Mo. This study highlights the efficiency of diffusion multiples for non-trivial materials' discovery and design. Graphical abstract: Highlights: Beta Ti alloy libraries have been generated in using the high throughput methodology of diffusion multiples. Solution hardening of Mo, Cr and V were evaluated via micropillar compression in single crystals with varied compositions Strain in all bcc-Ti crystals was accommodated by elementary slip in {110} slip planes Anomalous slip in bcc-Ti crystals was demonstrated to be dependent on both orientation and composition